The effect of cannabis dry flower irradiation on the level of cannabinoids, terpenes and anti-cancer properties of the extracts. (October 2020) - Kovalchuk, Olga; Li, DongPing; Rodriguez-Juarez, Rocio; Golubov, Andrey; Hudson, Darryl; Kovalchuk, Igor
Abstract: Flowers of Cannabis sativa contain many potentially therapeutic ingredients, including phytocannabinoids and terpenes. Consumption of cannabis requires drying and processing flowers which can potentially lead to accumulation of pathogens, including fungi and bacteria. In many countries, the level of pathogens in dried flowers is strictly regulated and thus, licensed cannabis cultivators irradiate dry flowers to decrease the chance of accumulation of pathogens. We have hypothesized that irradiation of flowers may change the level of active ingredients in flowers. We have tested the effect of gamma-radiation on the level of cannabinoids and terpenes in four varieties of cannabis. Plants were grown to maturity and flowers were harvested. One flower sample per variety was irradiated with 5 kGy using electron beam, while another sample was mock-treated. Cannabinoids were analyzed using HPLC and terpenes using GC-FID. Ethyl acetate was used to prepare extracts from two sets of flowers and extracts were tested for anti-proliferative capacity using methyl-thiazolyl-tetrazolium (MTT) assay on four different cancer cell lines, BJ-5ta, BT16, HCC1806 and IMR5. Solvent-based extraction of irradiated flowers showed slight increase in the total amount of solute. Irradiation of flowers resulted in the increased level of cannabinoids in the extract, more prominent in delta-9-tetrahydrocannabinol. There was also an increase in terpenes content in some cultivars. MTT assay showed that irradiation of flowers changed anti-cancer properties of three out of four tested extracts. Our experiments demonstrated that irradiation of flowers changes the amount of active ingredients in the extract and anti-cancer properties of such extracts.